Combined intravenous and intra-arterial thrombolysis in hyperacute cerebral ischemia without significant corresponding vascular occlusion/stenosis: A Preliminary investigation - Xinming Li; Yan Tan; Jinzhao Song; Hongying Lu; Yuan Bian; Wenqiang Cai (Heliyon, 2024)
Objective: In this study, we assessed the efficacy and safety of various thrombolytic treatment protocols in patients with hyperacute cerebral infarction. Methods: Patients diagnosed with acute ischemic stroke within 6 h of symptom onset and with brain computer tomography angiography confirming the absence of major vessel stenosis or occlusion were eligible for this study. The enrolled patients were subsequently randomized into two groups: all the groups received the standard intravenous thrombolysis treatment with rt-PA (0.9 mg/kg), and the experimental group underwent sequential intra-arterial thrombolysis treatment with alteplase (0.3 mg/kg, with a maximum dose of 22 mg), administered directly into the target vessel via a microcatheter. Both groups were closely monitored for changes in their National Institutes of Health Stroke Scale (NIHSS) score, modified Rankin scale score, hemorrhage rate, all-cause mortality rate, and the rate of favorable outcomes at 90 ± 7 days. Results: Ninety-four participants were enrolled in this study, with both the control and experimental groups initiating intravenous injection of rt-PA at a median time of 29 min. For the experimental group, the median time for arterial puncture was 123 min. Baseline data for both groups were similar (P > 0.05). Hemorrhagic transformation occurred in 24.47 % (23 patients), with a lower intracranial hemorrhage rate observed in the experimental group compared to the control group (15.2 % vs 33.3 %, P < 0.05). Asymptomatic hemorrhage rates were 8.7 % for the experimental group and 12.5 % for the control group, with no hemorrhage detected in other locations. Post-treatment median NIHSS scores were lower in the experimental group than in the control group (7 vs 9, P < 0.05), but short-term NIHSS scores were similar (P > 0.05). A higher proportion of patients in the experimental group achieved favorable outcomes compared to the control group (87.0 % vs 43.8 %, P < 0.05). Conclusion: In patients with acute ischemic stroke with an onset time of ≤6 h and no major intracranial vessel occlusion, combining rt-PA intravenous thrombolysis with intra-arterial thrombolysis via a microcatheter might yield superior functional outcomes.